Synergistic enhancement of mechanical property of the high replacement low-calcium ultrafine fly ash blended cement paste by multiple chemical activators. (November 2020) - Liu, Baoju; Shi, Jinyan; Liang, Hui; Jiang, Junyi; Yang, Yuanxia; He, Zhihai
Abstract: Although the alkali activation of fly ash (FA) has been well investigated, the composite application of multiple chemical activators has not been well explored in the high replacement (50% in mass) low-calcium ultrafine FA blended cement (FABC) paste. This study investigated the mechanical enhancement effect of multiple salt activators (CaCl2, Na2 SO4 and CaSO4 ·2H2 O) on the FABC paste, and compared with the most widely used alkaline activator (NaOH and Ca(OH)2 ). The activation mechanisms were analyzed by non-evaporated water content, pH value, XRD and SEM test. The results have shown that the compound activator has a more obvious strength gain for the FABC paste and is higher than that of the control group and the alkali-activated group, which benefits from the higher non-evaporated water content, a mild and lasting alkaline environment (pH value). In addition, the compound activator can play each role of its components, making FA particles participate in hydration reaction earlier. In terms of the cost and environmental impact, FABC paste activated by composite activators is more economical and cleaner than that activated by single alkali and control paste. This paper provides the guidance for the preparation of FABC paste with low alkalinity, high-benefits and eco-friendly. Graphical abstract: Image 1 Highlights: The high replacement low-calcium ultrafine FABC paste mixed with multiple activators was studied. Ca(OH)2, NaOH, CaCl2, Na2 SO4 and CaSO4 ·2H2 O were used to enhance mechanical properties of the FABC paste. The FABC paste mixed with composite activator has the best mechanical properties, cost and environmental impact.